TECHNOLOGIES FOR DEVELOPMENT OF CREATIVE COMPETENCE OF FUTURE TEACHERS - Yo‘ldosheva Dilfuzaxon Alisher qizi (Journals Park Publishing, 2023)
This article talks about innovative forms of teaching, tools for creativity development, modern creative methods proposed for use in lectures and practical training in the development of creative competence of future teachers.
Keywords: creativity, pedagogy, education, technology, upbringing, competence, lecture, seminar, research, innovation, personal development, ability, teacher, student, acmeology.